Digital Activism pada Platform Komunitas Fandom: Studi Netnografi pada ARMY di Weverse - Agustiana, Navi Dwi; Kusuma, Ade (DEPARTEMENT OF COMMUNICATION AND ISLAMIC BROADCASTING STUDIES, 2023)
The global success of BTS has always been associated with ARMY, which is the fandom of BTS itself. One of the platforms used by ARMY to gather and carry out digital fandom activities is Weverse. This research was conducted to find out how digital activism is carried out by ARMY on Weverse. This is due to remembering ARMY's strength as a fandom that was able to help BTS achieve success at the international level and side by side with western musicians, as the first Asian musician to be able to achieve this achievement. So, with these powers it is possible for the emergence of digital activism to encourage the existence of a certain social movement in order to achieve goals. This study uses a qualitative approach with netnography methods to determine fan activity and culture formed in digital communities. The researcher made participant observations of the activities carried out by ARMY on Weverse. From the data that has been collected and analyzed, the researchers found that there are digital activism activities as part of the implementation of digital fandom. The digital fandom activities are in the form of efforts to build closeness, production of various content, dissemination of information, holding various campaigns, and making lists of targets and goals. Digital activism carried out by ARMY is in the form of carrying out promotional campaigns and social campaigns. This campaign was carried out to support BTS to maintain their position in the music industry while maintaining their image as musicians who care about social issues.